2004
DOI: 10.1007/s00167-004-0561-1
|View full text |Cite
|
Sign up to set email alerts
|

Infrapatellar fat pad pressure and volume changes of the anterior compartment during knee motion: possible clinical consequences to the anterior knee pain syndrome

Abstract: This biomechanical study was performed to measure tissue pressure in the infrapatellar fat pad and the volume changes of the anterior knee compartment during knee flexion-extension motion. Knee motion from 120 degrees of flexion to full extension was simulated on ten fresh frozen human knee specimens (six from males, four from females, average age 44 years) using a hydraulic kinematic simulator (30, 40, and 50 Nm extension moment). Infrapatellar tissue pressure was measured using a closed cell sensor. Infrapat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 33 publications
1
52
0
Order By: Relevance
“…Some preliminary studies reported that signs of inflammation in IPFP (assessed using dynamic contrast-enhanced MRI) were cross-sectionally associated with knee pain in obese patients with knee OA,43 and inflammation and oedema of IPFP contributed to knee pain43 44 Oedema within IPFP could increase pressure and lead to irritation of nearby tissues such as knee capsule and nociceptive nerve fibres that contain substance-P,45 46 resulting in increased knee pain. Our current study reported that, cross-sectionally, IPFP signal intensity alteration was positively associated with knee pain (especially when going upstairs/downstairs, at night while in bed and when sitting or lying).…”
Section: Discussionmentioning
confidence: 99%
“…Some preliminary studies reported that signs of inflammation in IPFP (assessed using dynamic contrast-enhanced MRI) were cross-sectionally associated with knee pain in obese patients with knee OA,43 and inflammation and oedema of IPFP contributed to knee pain43 44 Oedema within IPFP could increase pressure and lead to irritation of nearby tissues such as knee capsule and nociceptive nerve fibres that contain substance-P,45 46 resulting in increased knee pain. Our current study reported that, cross-sectionally, IPFP signal intensity alteration was positively associated with knee pain (especially when going upstairs/downstairs, at night while in bed and when sitting or lying).…”
Section: Discussionmentioning
confidence: 99%
“…29,33 Symptomatically, irritation of the fat pad (often called the Hoffa syndrome) produces a dull, aching pain that is exacerbated by squatting, kneeling, climbing stairs, or prolonged sitting. 27,29,34,35 We found a prevalence of fat pad irritation of 0.4%.…”
Section: Discussionmentioning
confidence: 66%
“…In previous biomechanical studies we showed that an infrapatellar fat pad edema significantly increases tissue pressure inside the anterior knee compartment [1,2]. In a further immunohistochemical study, a high number of pain afferent substance-P nerve were found inside the fat pad adjacent to vessels [3], which we interpreted as a possible mechanism for inducing anterior knee pain following a possible chronic neurohistogenic fat pad edema.…”
Section: Discussionmentioning
confidence: 97%